Representation of Identity Crisis in Mohsin Hamid’s The Reluctant Fundamentalist - Adhikari, Rashmi Thapa (Patan Prospective Journal, 2023)
This paper underscores the existential status of the immigrants in the United States of America as portrayed in Mohsin Hamid’s The Reluctant Fundamentalist written as a response to the 9/11 attacks occurred on 11 September 2001. In the post-9/11 situation, the identity of Pakistani immigrants is more at risk than before because of the perpetrators’ religious identity as widely perceived to be extreme. Being Pakistani means being part of a society divided into different groups that are at odds with each other over religious, sectarian and political issues. In such a situation, where Pakistan does not only fight a war against terrorism but is a victim of terrorism as well, it is simply impossible to have a single national identity. Not only at home Pakistanis suffer the repercussions of terrorism but also in the United States of American as depicted in the text. The characters cast in the novel represent different ethnic groups of people who reside in the United States of America. They are divided into liberals. However, only Muslim characters seem excluded from society. They are treated as others in the land of democracy. They feel homeless and suffer existential crisis. The paper has aimed at exploring the causes of identity crisis in the novel. The event of September 11 changed the way the Islamic world views fundamentalists and terrorists. The obsession of Hamid is the loss of values, religious and political exploitation of the masses, suicide bombings and sectarianism, and the consequent evolution of individual identity perception in an alienating social framework.